2022
DOI: 10.1159/000526318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Pharmacologic Agents in the Management of Hemodynamically Significant Patent Ductus Arteriosus in Preterm: A Network Meta-Analysis and Risk-Benefit Analysis

Abstract: <b><i>Introduction:</i></b> Various pharmacological treatments are available for preterm infants with patent ductus arteriosus (PDA), but their risks and benefits are controversial. This study aimed to identify the best treatment for PDA using network meta-analysis (NMA) and risk-benefit assessment (RBA). <b><i>Methods:</i></b> Relevant randomized controlled trials (RCTs) were identified from MEDLINE, Scopus, and the Cochrane Library. RCTs were eligible if they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 101 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…Another meta-analysis of 70 studies evaluated the efficacy and safety of various treatment options for PDA closure [ 32 ]. They found that high-dose oral ibuprofen is the best pharmacological treatment option for PDA closure in preterm and term infants with hsPDA [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis of 70 studies evaluated the efficacy and safety of various treatment options for PDA closure [ 32 ]. They found that high-dose oral ibuprofen is the best pharmacological treatment option for PDA closure in preterm and term infants with hsPDA [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another meta-analysis of 70 studies evaluated the efficacy and safety of various treatment options for PDA closure [ 32 ]. They found that high-dose oral ibuprofen is the best pharmacological treatment option for PDA closure in preterm and term infants with hsPDA [ 32 ]. These findings were further replicated by another systematic review, which found that high-dose oral ibuprofen has greater efficacy in patients with hsPDA as compared to standard-dose ibuprofen or IV indomethacin [ 8 ].…”
Section: Reviewmentioning
confidence: 99%